Pengaruh Media Gambar Terhadap Hasil Belajar IPA Siswa Kelas III Sekolah Dasar di Desa Bener Kecamatan Majenang - Risa Puspita Oktiana; Fita Permata Sari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Picture media is a learning tool used by teachers to make it easier when explaining subject matter using pictures. This study was conducted to determine the effect of image media on science learning outcomes for third grade elementary school students in Bener Village, Majenang District. The type of research used is experimental research with a quantitative approach. The research method used is Quasy Experimental. The population in this study were third grade elementary school students in Bener Village, Majenang District. The sample used in this study is a saturated sample. The results showed that the significance value in the experimental class was 0.000<0.05 and the significance value in the control class was 0.001<0.05. means that there is a significant influence between student learning outcomes before and after using image media on third grade elementary school students in Bener Village, Majenang District.